PEMANTAPAN SURVEY PENGUKURAN DAN PEMETAAN DIGITAL BAGI GURU DAN SISWA SMK NEGERI 1 SIDOARJO - Nusantara, Danayanti Azmi Dewi; Mochamad Firmansyah Sofianto; Wulandari, Meity; Abdiyah Amudi; Lynda Refnitasari; Desy Ratna Arthaningtyas (Universitas PGRI Adi Buana Surabaya, 2024)
The role of measurement and mapping science in the construction sector is very important. The development of tools used for survey measurements and mapping is now in digital form. The application of land surveying knowledge can not only be obtained at universities but can also be obtained at Vocational High Schools (SMK) which have majors in the field of construction. To improve the quality of learning, competence and skills in the field of land surveying, training can be carried out. This training is a form of Community Service (PKM) which can be carried out by lecturers from the Civil Engineering Undergraduate Study Program. The partner in this PKM is SMK Negeri 1 Sidoarjo where training will be provided in measuring surveys and digital mapping. Adequate skills will be created if teaching staff and educational staff have adequate competence